Stabilitas Agregat Tanah, Populasi Jamur Pelarut P dan Hasil Jagung yang Dipengaruhi oleh Pupuk Hayati Mikroba Pelarut P dan Pupuk P pada Ultisols - Betty Natalie Fitriatin; Muhammad Agi Pratama; Oviyanti Mulyani (Fakultas Pertanian Universitas Padjadjaran, 2018)
Ultisols is a soil order with low available P. Phosphate Solubilizing Microbes is a group of microorganisms that has the ability to release P for plants. The aim of this experiment was to determine effect of phosphate solubilizing microbes and P fertilizer on soil aggregate stability, PSF population and yield of maize (Zea mays L.) on Ultisols. This research was conducted from May 2016 to August 2016 at Ciparanje, Faculty of Agriculture, Universitas Padjadjaran. This research was arranged in Randomized Block Design (RBD), consisted of 9 treatments with 3 replications. The treatments were 100 kg ha-1 of SP-36 fertilizer, 50 kg ha-1 of biofertilizer, as well as combination of SP-36 fertilizer (50% and 100%) with the dose of biofertilizer (50%, 100% and 150%). This experiment showed that the combination of biofertilizer and P fertilizer gave significant effect on the population of PSF and yield of maize, but not for stability of soil aggregates. The application of SP-36 50 kg ha-1 and 50 kg ha-1 PSM combination gave higher population of PSF and yield of maize.Keywords: Biofertilizer, maize, phosphate- solubizing fungi, aggregate stability, Ultisols